2017
DOI: 10.1515/ace-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Operation of 2+1 Road with High Shares of Heavy Vehicles

Abstract: The author investigated traffic flow quality on a new 2+1 long road bypass with an exceptionally high share of heavy vehicles in order to assess rational limits of heavy vehicle shares in traffic flow, dependent on the length of the 2+1 road and the number of passing segments in each direction. This paper presents the results of traffic flow quality analyses through the use of empirical and simulation methods for a single 2+1 road segment with additional passing lanes, as well as for the study of the entire se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In addition, they provided, with other researchers, a method for determining passing lanes' operational efficiency in terms of enhanced service [14,15]. Kieć (2017) simulated the effect of heavy vehicles (HVs) shares (up to 20%) in the traffic stream of a 2+1 long road bypass, using PTV VISSIM [16], and found that the 2+1 system appears to be reasonably effective when compared to the TLTW bypass for traffic volumes up to an average annual daily traffic (AADT) of 22,000 [17]. Furthermore, Kirby et al (2014) recommended that speed limits for the 2+1 design be between 80 and 100 km/h [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they provided, with other researchers, a method for determining passing lanes' operational efficiency in terms of enhanced service [14,15]. Kieć (2017) simulated the effect of heavy vehicles (HVs) shares (up to 20%) in the traffic stream of a 2+1 long road bypass, using PTV VISSIM [16], and found that the 2+1 system appears to be reasonably effective when compared to the TLTW bypass for traffic volumes up to an average annual daily traffic (AADT) of 22,000 [17]. Furthermore, Kirby et al (2014) recommended that speed limits for the 2+1 design be between 80 and 100 km/h [9].…”
Section: Introductionmentioning
confidence: 99%
“…The application of microsimulation conflicts is considered as one of the methods that are based on surrogate safety measures, which permit the estimation of the number of conflicts for different road and traffic configurations [6], [7], [8], [9], [10]. Such an approach is much more popular when analyzing intersections and, although simulation modelling of road sections with additional lanes has been described in the literature, these studies mainly discuss modelling in the context of evaluating operation and traffic performance [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%